Technical Efficiency of Soft Drink Manufacturing Industry in Malaysia - Ahmad Izzat Mohd Idris; Mohd Fahmy Abdullah; Lai Wei Sieng (International Journal of Supply Chain Management, 2019)
The previous studies on technical efficiency (TE) of the soft drinks industry in Malaysia are still under consideration from other industries and existing studies discuss the industry in general. In fact, there is a previous study using industry-level data and does not consider the determinants of technical inefficiency determining the TE level. The purpose of this study is to identify the technical efficiency level and the technical inefficiency of the soft drinks manufacturing industry in Malaysia by 2015 using cross-section data of 118 firms obtained from the Department of Statistics (DOS). Based on the analysis method of stochastic analysis (SFA), the results showed that the level of technical efficiency was high. As a result, inefficient technical analysis finds that salary rates reduce inefficiencies and the ratio of capital workers increases inefficiencies. The basic implication of this study is that soft drinks manufacturing firms need to increase motivation among employees and strengthen network market production through pay increases.